Analytical model for optimal data transmission policy in two-way relay network coding under phase type arrivals - Gunasekara, Charith (IET communications, 2019)
The authors consider a scenario in which two wireless nodes communicate via a single access-point with two buffers using network coding. The access point first pairs each data packet being sent from each node and then performs the network coding operation. Packets arriving at the access point that are unable to be paired are instead loaded into one of the two buffers at the access point. When one of the buffers is empty and the other is not, network coding is not possible. When this happens, the access point must either wait for a network coding opportunity, or transmit the unpaired packet without coding. The authors analyse the trade-off that arises between decreasing packet delay time, and increasing efficiency of the wireless spectrum usage as double-ended push-out queueing theory problem under phase type data arrivals. They use this model to resolve the optimal threshold policy and analyse the performance of the system.